Progress Toward Fabrication of Machined Metal Shells for the First Double-Shell Implosions at the National Ignition Facility. (3rd April 2018) - Cardenas, Tana; Schmidt, Derek W.; Loomis, Eric N.; Randolph, Randall B.; Hamilton, Christopher E.; Oertel, John; Patterson, Brian M.; Henderson, Kevin; Wilson, Doug C.; Merritt, Elizabeth; Montgomery, David; Daughton, William; et al.
Abstract: The double-shell platform fielded at the National Ignition Facility requires developments in new machining techniques and robotic assembly stations to meet the experimental specifications. Current double-shell target designs use a dense high-Z inner shell, a foam cushion, and a low-Z outer shell. The design requires that the inner shell be gas filled using a fill tube. This tube impacts the entire machining and assembly design. Other intermediate physics designs have to be fielded to answer physics questions and advance the technology to be able to fabricate the full point design in the near future. One of these intermediate designs is a mid-Z imaging design. The methods of designing, fabricating, and characterizing each of the major components of an imaging double shell are discussed with an emphasis on the fabrication of the machined outer metal shell.